The promotion plan for overseas education of Castilho Soares - Carvalho, C.; Barreto, M. (Connecting Narratives of Education in Times of Colonization and Post-Independence in Africa (1920s - 1970s), 2024)
História da educação colonial em Angola e o papel de Amadeu Castilho Soares